El Endurecimiento de las medidas Socio-Educativas a los Menores Infractores como sujetos activos del Delito - Ortega Córdova, Pablo Alexander (2016)
The subject of study is highly relevant, since the minority, as grounds for exemption separated from the other alleged responsibility and a specific provision, is also in a way and within certain limits a cause of the lack of hardening of the socio-educational measures for juvenile offenders and perpetrators of the crime; based on the lack of maturity of the child who lacks sufficient capacity to motivate by the rules. However, the lack of hardening of the socio-educational juvenile offenders, measures does not allow to establish the basis of criminal responsibility as perpetrators of the crime, leading to not be accountable juvenile offenders if we stress on the criterion of imputability to exclude the criminal responsibility of minors but only and exclusively to exclude such liability under criminal organic whole code. And, the child is able to understand the meaning of the crime he has committed and act accordingly, but the principle of guilt must be adapted to their peculiar psychology and / or degree of maturity, and in this way to toughen sanctions juvenile offenders and not let defenseless victims. The period of adolescence is characterized by ambiguity at all levels regarding behavior, social norms, the relationship with others and with oneself, generally everything is marked by contradiction and divergence. The reality of this stage is so obvious that sometimes we let ourselves be blinded by their proximity. We forget that the concept of "adolescence" is 5 relatively recent, and much remains to study and learn from such a changing existence, subject to constant social, technical and economic adjustments. It's hard to be objective with teenagers, but we must not forget that young people around us have been trained in an environment in which we have participated in greater or lesser extent and, moreover, they are intended to gradually replace us. Adolescence is characterized by the culture of immediacy, by emotional instability, the need to know, experiment and test both the resistance itself, as the limits and family and social norms, considered a stage of evolutionary crisis. At the same time aware of the existing problem of juvenile offenders that cause in society one is to increase the level of crime in society, not having a decent social security to people, it is why Anotare legal bodies as: The Constitution of the Republic of Ecuador, the Code of Children and adolescents, rules that protect directly to the rights of adolescent